COMPARATIVE ANALYSIS OF HEMATOLOGICAL INFLAMMATORY BIOMARKERS IN VACCINATED AND UNVACCINATED COVID-19 PATIENTS IN HYDERABAD SINDH (Journal of Medical & Health Sciences Review, 2025)
COVID-19's severity links to out-of-control inflammatory responses. The Neutrophil-to-Lymphocyte Ratio (NLR) and Lymphocyte-to-C- Reactive Protein Ratio (LCR) stand in for systemic inflammation and immune status. To compare NLR, LCR and inflammatory markers among vaccinated vs non-vaccinated. An observational cross-sectional study of 256 subjects (156 unvaccinated, 100 vaccinated). Demography, symptoms and laboratory parameters were compared with the independent t-test, chi-square and ANOVA. Vaccinated individuals showed significantly lower NLR (2.41 ± 1.12 vs 6.52 ± 3.84, p